The effect of biological maturation on foot morphology, and their relation to postural stability performance in male footballers - Fallon Verbruggen, Ferdia; Kaľata, Maroš; Marenčáková, Jitka; Malý, Tomáš; Zahálka, František (The Journal of sports medicine and physical fitness, 2023)
BACKGROUND: Biological maturity (BM) and foot morphology (FM) can independently alter neuromuscular loading on the ankle-foot complex, potentially causing stability deficits and injury predisposition. However, the influence of BM on FM, and how much both explain neuromuscular performance in postural stability (PS) tests, has been understudied. This study aimed to investigate the effect of BM on FM, and then discover to what extent both factors explain the variance in PS performance in adolescent footballers. METHODS: Over one season, 399 three-dimensional foot scans were gathered from 72 footballers (U12-U15). PS was measured by center of pressure (COP) displacement in bilateral and unilateral stance. The Khamis and Roche equation determined maturity status (MS), while formulae from Mirwald and Khamis and Roche estimated timing of biological maturation (TBM). Principal component analysis determined nine principal components that explained the most variance in FM. An ANCOVA determined the effect of TBM on FM principal components, with covariates of age, height, weight, playing position, and foot preference. Step-wise linear regression determined the explanation of COP displacement by the above-mentioned predictors. RESULTS: There was significantly increased foot pronation during and after peak height velocity/puberty. MS and four foot principal components (foot arch and width, great toe width and length) were significant predictors in all PS tests (R2: 0.105-0.180). CONCLUSIONS: TBM had a significant effect on FM presentation, and should be a part of adolescent foot assessment. While they only explained a small amount of variance, determining MS and FM may identify those requiring additional PS attention.
Keywords: posturální rovnováha; Adolescent; lidé; Humans; hlezenní kloub; dolní končetina; Postural Balance; mužské pohlaví; kotník; Ankle; mladiství; Ankle Joint; Male; Lower Extremity